2017
DOI: 10.1186/s12876-017-0610-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with network meta-analysis: dual therapy for high-risk bleeding peptic ulcers

Abstract: BackgroundAdding a second endoscopic therapy to epinephrine injection might improve hemostatic efficacy in patients with high-risk bleeding ulcers but the optimum modality remains unknown. We aimed to estimate the comparative efficacy of different dual endoscopic therapies for the management of bleeding peptic ulcers through random-effects Bayesian network meta-analysis.MethodsDifferent databases were searched for controlled trials comparing dual therapy versus epinephrine monotherapy or epinephrine combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Two recent meta-analyses support the superiority of combination endoscopic therapy (injection plus thermal therapy, and injection plus mechanical therapy) over epinephrine injection monotherapy in peptic ulcers with high risk stigmata [124,125]. Baracat et al performed a systematic review and metaanalysis of 28 RCTs that included 2988 adults with high risk peptic ulcer endoscopic stigmata.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent meta-analyses support the superiority of combination endoscopic therapy (injection plus thermal therapy, and injection plus mechanical therapy) over epinephrine injection monotherapy in peptic ulcers with high risk stigmata [124,125]. Baracat et al performed a systematic review and metaanalysis of 28 RCTs that included 2988 adults with high risk peptic ulcer endoscopic stigmata.…”
Section: Recommendationmentioning
confidence: 99%
“…No significant difference in mortality between hemostasis modalities was observed. In a network meta-analysis, Shi et al reported that the addition of mechanical therapy following epinephrine injection significantly reduced the probability of rebleeding and surgery (OR 0.19, 95 %CI 0.07-0.52 and OR 0.10, 95 %CI 0.01-0.50, respectively), while the addition of thermal therapy only reduced ulcer rebleeding rates (OR 0.30, 95 %CI 0.10-0.91) [125].…”
Section: Recommendationmentioning
confidence: 99%
“…In a Cochrane review including 19 randomized studies and 2033 patients, Vergara et al [104] has shown that additional endoscopic treatment after epinephrine injection reduces further bleeding and the need for surgery in patients with highrisk bleeding peptic ulcer; however, they cannot conclude that a particular form of dual-modality treatment is equal or superior to another. Shi et al have performed a network meta-analysis on dual therapy choices [105] and shown that the addition of mechanical therapy after epinephrine injection significantly reduced the probability of rebleeding (OR 0.19, 95% CI 0.07-0.52) and surgery (OR 0.10, 95% CI 0.01-0.50). Epinephrine with thermal therapy was shown to reduce the rebleeding rate (OR 0.30, 95% CI 0.10-0.91) but not the need for surgical intervention (OR 0.47, 95% CI 0.16-1.20).…”
Section: Non-operative Management-endoscopic Treatmentmentioning
confidence: 99%
“…For prevention of bleeding in "difficult" pedunculated polyps (with head ≥2 cm or a stalk ≥1.5 cm), injection of dilute adrenaline and/or mechanical hemostasis is recommended [15]. It has been shown that the use of endoloops or endoclips (mechanical prophylaxis) can be superior to adrenaline injection and combination of mechanical prophylaxis with adrenalin injection significantly decreased post polypectomy bleeding in comparison with injection alone [21][22][23]. ESGE recommends that large (≥2 cm), sessile and laterally spreading "difficult" polyps should be always treated and removed by trained and experienced endoscopist in appropriately resourced tertiary endoscopic centre.…”
Section: Conventional Polypectomymentioning
confidence: 99%